Biomass‐derived Graphene‐like Catalyst Material for Oxygen Reduction Reaction. Issue 3 (11th February 2021) - Kaare, Kätlin; Yu, Eric; Käämbre, Tanel; Volperts, Aleksandrs; Dobele, Galina; Zhurinsh, Aivars; Niaura, Gediminas; TamasauskaiteTamasiunaite, Loreta; Norkus, Eugenijus; Kruusenberg, Ivar
Abstract: A novel and sustainable method was established to prepare a nitrogen doped graphene‐like material from a renewable, secondary raw material with potential application in the catalysis of oxygen reduction reaction (ORR). Alder wood char was used as a precursor material for producing a sustainable graphene‐like carbon catalyst for the ORR. Alder wood char was first activated (AWC) and then doped with nitrogen (N−AWC). The graphene‐like structure was confirmed using transmission electron microscopy (TEM) and Raman spectroscopy. Electrochemical characterization was carried out in 0.1 M KOH, showing that in alkaline media the ORR activity of the N‐doped wood char‐based graphene‐like material is superior compared to non‐sustainable commercial N‐doped graphene. The onset potential of the ORR on N‐AWC was shifted to positive direction by 75 mV in comparison to the commercially available nitrogen‐doped graphene and the half‐wave potential was shifted even by 239 mV. This renewable biomass‐derived graphene‐like carbon catalyst shows a great potential alternative to current synthetic graphite, graphene nanoplatelets and graphene materials in areas such as fuel cells and batteries. Abstract : Biomass was converted into a N‐doped graphene‐like carbon nanomaterial. As biomass is renewable, it is possible to produce carbon in a sustainable way. The material was further studied as a catalyst material for the oxygen reduction reaction and it showed exceptional electrochemical activity towards the ORR compared to commercial N‐doped carbon.